The Mediation Effects of Innovation Capabilities and Competitive Advantages on Social Capital to the Success of Community Enterprise Performance in the Southern Border Provinces of Thailand - Soonsuwon, Kornkamol; Jankingthong, Wiwat; Sangkapan, Jedsarid (Hatyai Academic Journal, 2024)
This research aimed: 1) to examine factors affecting the success of community enterprise performance in Thailand’s Southern Border Provinces and 2) to investigate the mediating effects of innovation capabilities and competitive advantages on social capital for the success of community enterprises in the Southern Border Provinces. This was a quantitative research study using a questionnaire as the research tool. A sample size of 400 individuals was obtained, and questionnaires were collected from community enterprises in the Southern Border Provinces of Thailand. Data were analyzed by using the LISREL program. The structural equation model showed goodness of fit with the empirical data, which found that χ2= 125.10 χ2/df = 3.38 RMSEA = 0.077 NNFI = 0.96 CFI = 0.97 and SRMR = 0.047. The research found that 1) innovative capability directly affected the performance of community enterprise; 2) competitive advantage directly affected the performance of community enterprise; and 3) social capital indirectly affected the performance of community enterprise through innovative capability and competitive advantages. The results can be used as guidelines for community enterprises in the Southern Border Provinces of Thailand to sustain their success through improved performance.